The development of plural expressions in a Malay-English bilingual child - Mohamed Salleh, Rabiah Tul Adawiyah; Kawaguchi, Satomi; Jones, Caroline; Di Biase, Bruno (International Islamic University Malaysia, 2016)
In a postcolonial country such as Malaysia, English plays an important role in governance, education and popular culture. With English now becoming the lingua franca of the globalised world, many Malaysian urban families use English to speak to their children at home, in conjunction with the Malay language or other ethnic languages. Recognising the important relationship between the two languages, this paper investigates early bilingual development of Malay and English focusing specifically on the development of plural marking in a child raised simultaneously in these typologically distant languages. These two languages express plurals differently: Malay through various forms of reduplication and English by morphological marking on nouns. But how does the child manage to learn, simultaneously, such divergent systems? In order to shed some light on this question, a bilingual child growing up in these two languages was audio- and video- recorded in each language over 6 months, that is from 3 years 4 months (3;4) to 3 years 10 months (3;10). Results suggest that though the child appeared to develop two distinct systems of plurality in Malay and English, the two developing systems also manifested considerable cross-linguistic influence in both directions. Implications for the study of world Englishes are discussed.